Eichhornia crassipes mediated bioinspired synthesis of crystalline nano silver as an integrated medicinal material: a waste to value approach - Moudgil, Aliesha; Deval, Animesh S.; Dharne, Mahesh S.; Sarkar, Dhiman M.; Choudhari, Amit S.; Chaudhari, Bhushan P. (Journal of Cluster Science, 2021)
The present study deals with the synthesis of silver nanoparticles from Eichhornia crassipes. Dynamic light scattering (DLS), Transmission electron microscopy (TEM), UV-Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed for nanoparticle characterization. The aqueous plant extract of Eichhornia crassipes was phytochemically analyzed for phenol, flavonoid, reducing sugar content, alkaloids, saponins and carotenoids. The synthesized particles after optimization of important parameters have an average diameter of 12.48 +/- 3.43 nm with a spherical morphology and zeta potential of - 31.53 mV. At 100 mu g/ml of nanoparticle concentration, the antioxidant activity of 93.6% was observed. MIC (Minimum inhibitory concentration) values exhibiting the antimicrobial attributes reported an estimated value of 7.8 mu g/ml for gram-negative and higher values of 31.25 and 250 mu g/ml for gram-positive bacteria. The antibiofilm assay showed 86.89% and 74.7% of the reduction in violacein synthesis and biofilm inhibition respectively at 15 mu g/ml nanoparticle concentration. The anticancer assay reported the IC50 (Inhibitory concentration) values of 13.32, 14.71 and 19.91 mu g/ml for HeLa, HCT 116 and L6 cell lines respectively. Thus the study establishes a significant integrative treatment to combat secondary infections in cancer patients. Graphic
Keywords: antibacterial activity; Antibiofilm activity; Anticancer activity; Antioxidant activity; Eichhornia crassipes; silver nanoparticles